The Assessment of the Liquidity of Agricultural Farms in Poland on the Background of the European Union in the Years 2009-2015 - Ryś-Jurek, Roma (Studia Oeconomica Posnaniensia, 2018)
The aim of the study was an analysis of the liquidity of agricultural farms in Poland on the background of the European Union. The FADN statistical data was mainly used. That enabled the analysis of the phenomenon by the countries of the European Union in the years 2009-2013 and in layouts by economic size and type of farming. A study was also performed for the Polish regions of FADN.